An Assessment of Risk-Taking Behavior of Individual Investors: Role of Financial Literacy and Emotions - Shaikh, Ayisha; Khan, Matloob Ullah (International Journal of Economics and Financial Issues, 2024)
This paper studies the impact of emotions such as locus of control, overconfidence, risk avoidance, agreeableness, and financial literacy on risk-taking behavior. Data was collected from 338 individual investors from Delhi-NCR and analyzed through PLS-SEM 4 (V.4.0.9.2) to understand the direct and inverse association among the construct and to identify what influenced their investment choices the most. According to the data interpretation, a strong association between agreeableness and risk-taking behavior was evident; the study’s findings indicate that investors were heavily impacted by their peer group while making investment decisions. It also concludes that financial literacy induces overconfidence but does not result in risk-taking behavior. General risk aversion has a direct and locus of control has an indirect influence moderated by agreeableness on the risk-taking behavior of individual investors.